О трехмерных начально-краевых задачах динамики толстых упругих плит - Стоян, В.А.; Волощук, С.Д. (Проблемы управления и информатики, 2021)
Розв’язано складні задачі тривимірної теорії пружності для товстих пружних плит з довільною геометрією їх бічної поверхні. Побудовано аналітичні залежності компонент поля пружних динамічних зміщень внутрішніх точок плити від гранично-поверхневих зовнішньо-динамічних збурюючих факторів, визначених неперервними функціями або векторами їх значень. The complex problems of the three-dimensional theory of elasticity for thick elastic plates with arbitrary geometry of their lateral surface have been solved. Analytical dependencies of the components of the elastic dynamic displacement field at the internal points of the plate have been constructed, depending on the boundary-surface external dynamic perturbation factors, defined by continuous functions or vectors of their values.